Using Recyclable Water Containment Areas (RWCAs) to Treat Agricultural Stormwater Runoff For Watersheds: A Concept Paper - Edward A. Hanlon (EDIS)
Retain water within the basin or watershed for the betterment of society, agriculture, and the environment. Develop a means by which private land owners/growers can benefit from assisting with the management of water at the watershed level for control of non-urban stormwater runoff, nutrient sequestering, and soil quality improvement. This document is SL227, a fact sheet of the Soil and Water Science Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date July 2005.